FLUORIDE ABSORBED ON EXTRACTED TEETH AFTER IMMERSING IN FLUORIDE TABLET, FLUOCOL SOLUTION AND FLUORIDE DENTRIFICE (IN VITRO TEST) - Diyah Fatmasari; Lanny Sunarjo (Odonto : Dental Journal, 2016)
Background: The role of fluoride in preventing tooth decay both for children and adult has been acknowledged internationally. There are several types of fluoride modalities either topically or systemic way. In Indonesia the modalities used to apply are fluoride tablet, fluocol solution and fluoride containing toothpaste. The purpose of this research is to find the effectiveness of fluoride modalities.Method: The study design was quasy experimental with 40 extracted teeth (Premolar teeth). The teeth divided into four groups D group I soaked on tablet fluor, Group II ; soaked on fluocol solution, Group III soaked on fluoride tooth paste and group IV soaked on Mill J (Aquadest/ Control solution). Fluoride concentration before and after soaking was determined using Spectrophotometer UV-Vis. Fluoride absorption was determined by the reduction of fluoride concentration after soaking.Result: Research result shown that the highest fluoride absorption was on soaking in fluoride tablet, followed by soaking on fluocol and tooth paste (mean fluoride absorption was 0,32; 0,08 and 0,04 ppm). Anova test shown significance level was 0,000.Conclusion: there were a significance of fluoride absorption on soaking in tablet fluoride, fluocol solution and toothpaste. The mechanism of fluoride regimens shown different fluoride absorption.